Enhancing tomato resistance by exploring early defense events against Fusarium wilt disease - Jingtao Li; Chenyang Wang; Limei Yang; Fahui Qiu; Yue Li; Yaning Zheng; Sihui Liu; Limin Song; Wenxing Liang (Phytopathology Research, 2023)
Abstract Studying plant early immunity, such as the unique immune mechanisms against pathogens, is an important field of research. Tomato wilt resulting from the infection by Fusarium oxysporum f. sp. lycopersici (Fol) is an important soil-borne vascular disease. In this study, we challenged tomato plants with Fol for a time-course RNA sequencing (RNA-seq) analysis. The result indicated that phenylpropanoid and flavonoid pathway genes were significantly enriched during the early invasion stage. Further study revealed that the flavonoids galangin and quercetin could effectively inhibit Fol growth and enhance wilt resistance in tomato. Moreover, the genes involved in plant-pathogen interactions, the MAPK signaling pathway, and plant hormone signal transduction were significantly enriched. These genes were also involved in plant pattern-triggered immunity (PTI) and effector-triggered immunity (ETI) signaling pathways. Strikingly, the transcription levels of pathogen-related protein 1 (SlPR1) were dramatically increased at 2 days post Fol inoculation, implying that SlPR1 is important in early immunity in tomato. SlPR1 does not have direct antifungal activity. Instead, its C-terminal peptide CAPE1 could activate root defense responses, such as the reactive oxygen species (ROS) burst, salicylic acid (SA)/jasmonic acid (JA) production, and defense-related gene expression, which collectively increased tomato resistance to Fol infection. In addition, CAPE1 could induce systemic acquired resistance (SAR). Application of CAPE1 onto tomato leaves induced local resistance to the pathogen Botrytis cinerea and systemic resistance to Fol infection. These results advanced our understanding for the early immunity against Fol in tomato and provide potential strategy for tomato disease control.